Group Guidance Based on Ibn Arabi's Cosmology for Students’ Self-Improvement: A Semantic Analysis on the Writing of Vocational High School Students in Purwokerto - Ramadhan Azkiya; Nur Azizah (G-Couns: Jurnal Bimbingan dan Konseling, 2026)
Today's teenagers need to be prepared to face self-development challenges that affect their motivation and sense of meaning in life. This study examines group guidance grounded in Ibn Arabi's cosmology to improve students' self-improvement through the semantic analysis of handwriting in vocational high schools. The research method uses a qualitative case study with handwriting documentation and in-depth interviews. The study subjects were five students from class XI MPLB 1 at State Vocational High School 1 Purwokerto. Data analysis was carried out semantically to reveal implied meanings and spiritual values. The study results showed that group guidance encouraged students to write about improving their quality of life, life skills, health, and continuous improvement, reflecting motivation and the meaning of life. Group guidance based on Ibn Arabi's cosmology can support students' self-improvement. Guidance and counselling teachers can develop a group guidance model based on Ibn Arabi's cosmology to more meaningfully support students' self-development. Keywords: group guidance, self improvement, ibn arabi cosmology, lexical semantics